Synergistic effect of bioactive lipid and condition medium on cardiac differentiation of human mesenchymal stem cells from different tissues - Jiang, L; Wang, Y; Pan, F; Zhao, X; Zhang, H; Lei, M; Liu, T; Lu, J (Wiley, 2016)
Human umbilical cord mesenchymal stem cells (hUCMSCs) and human adipose tissue mesenchymal stem cells (hATMSCs) have the potential to differentiate into cardiomyocytes, making them promising therapeutic candidates for treating damaged cardiac tissues. Currently, however, the differentiated cells induced from hUCMSCs or hATMSCs can hardly display functional characteristics similar to cardiomyocytes. In this study, we have investigated the effects of bioactive lipid sphingosine-1-phosphate (S1P) on cardiac differentiations of hUCMSCs and hATMSCs in condition medium composed of cardiac myocytes culture medium or 5-azacytidine. Cardiac differentiations were identified through immunofluorescence staining, and the results were observed with fluorescence microscopy and confocal microscopy. Synergistic effects of S1P and condition medium on cell viability were evaluated by MTT assays. Functional characteristics similar to cardiomyocytes were evaluated through detecting calcium transient. The differentiated hUCMSCs or hATMSCs in each group into cardiomyocytes showed positive expressions of cardiac specific proteins, including α-actin, connexin-43 and myosin heavy chain-6 (MYH-6). MTT assays showed that suitable differentiation time was 14 days and that the optimal concentration of S1P was 0.5 μM. Moreover, incorporation of S1P and cardiac myocytes culture medium gave rise to calcium transients, an important marker for displaying in vivo electrophysiological properties. This feature was not observed in the S1P-5-azacytidine group, indicating the possible lack of cellular stimuli such as transforming growth factor-beta, TGF-β.